EDUCATIONAL AND COGNITIVE ACTIVITY OF STUDENTS IN ACCORDANCE WITH THEIR PHYSICAL AND MENTAL DEVELOPMENT (Spectrum Journal of Innovation, Reforms and Development, 2023)
This article explains the mechanisms of the development of mental abilities in the minds of students through engagement into physical culture and sports.